2008
DOI: 10.1002/jae.1003
|View full text |Cite
|
Sign up to set email alerts
|

Are output growth‐rate distributions fat‐tailed? some evidence from OECD countries

Abstract: This work explores some distributional properties of aggregate output growth-rate time series. We show that, in the majority of OECD countries, output growth-rate distributions are well-approximated by symmetric exponential-power densities with tails much fatter than those of a Gaussian. Fat tails robustly emerge in output growth rates independently of: (i) the way we measure aggregate output; (ii) the family of densities employed in the estimation; (iii) the length of time lags used to compute growth rates. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
136
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 62 publications
17
136
1
1
Order By: Relevance
“…We employ the same data set for which Duschl and Brenner (2013a) have observed a non-Gaussian (almost Laplacian) distribution of regional industry-specific employment growth rates (the data will be described in the next section). This finding can be connected to previous studies which found heavier-than-Gaussian tails in the empirical distributions of firm (sales and employment) growth rates (Stanley et al, 1996;Bottazzi et al, 2011), of industry (value added) growth rates (Castaldi and Sapio, 2008) and of country (aggregate output) growth rates (Fagiolo et al, 2008). Non-Gaussian distributions might in principle result from a stochastic process governed by Gaussian shocks (Brock, 1999).…”
Section: Methodssupporting
confidence: 82%
“…We employ the same data set for which Duschl and Brenner (2013a) have observed a non-Gaussian (almost Laplacian) distribution of regional industry-specific employment growth rates (the data will be described in the next section). This finding can be connected to previous studies which found heavier-than-Gaussian tails in the empirical distributions of firm (sales and employment) growth rates (Stanley et al, 1996;Bottazzi et al, 2011), of industry (value added) growth rates (Castaldi and Sapio, 2008) and of country (aggregate output) growth rates (Fagiolo et al, 2008). Non-Gaussian distributions might in principle result from a stochastic process governed by Gaussian shocks (Brock, 1999).…”
Section: Methodssupporting
confidence: 82%
“…17 Fagiolo et al (2008) find that GDP growth rates distributions are well proxied by double exponential densities, which dominate both Student's t and Levy-stable distributions. In light of such results, the choice of Curdia et al (2014) to drawn shocks from a Student's t distribution is not only ad-hoc, but not supported by the empirical evidence.…”
Section: Recent Developments In Dsge Modeling: Patches or Newmentioning
confidence: 95%
“…More generally, DSGE models can do well in "normal" time, but they cannot account for crises and deep downturns (Stiglitz, 2015). This is not surprising since macroeconomic time series distributions are well approximated by fat tail densities (Fagiolo et al, 2008) and DSGE models typically assume Gaussian distributed shocks. 10 Moreover, Ascari et al (2015) find that even fat-tailed Laplace shocks are assumed, the distributions of the time series generated by DSGE models have much thinner tails than those observed in real data.…”
Section: Empirical Issuesmentioning
confidence: 99%
“…More specifically, recession duration is exponentially distributed; GDP growth rate distribution is fat-tailed (Fagiolo et al, 2008), i.e. mild and deep downturns coexists; banking crises duration is right skewed and the distribution of their fiscal cost over GDP is fat-tailed.…”
Section: Macroeconomic Dynamics and Stylized Fact Replicationmentioning
confidence: 99%